1977
DOI: 10.1002/ajpa.1330460310
|View full text |Cite
|
Sign up to set email alerts
|

Functional implications of primate enamel thickness

Abstract: Recent evolutionary interpretations of Hominoidea have postulated functional relationships between tooth form, diet and masticatory biomechanics. A major consideration is the durability of the tooth under certain dietary conditions. Teeth with low cusps and thicker enamel are able to withstand heavy mastication of abrasive food bolus for a longer period. When comparisons are made between species of higher primates the variables of tooth size, cusp morphology, and enamel thickness appear to be related but until… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
107
0

Year Published

1995
1995
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 134 publications
(116 citation statements)
references
References 13 publications
9
107
0
Order By: Relevance
“…Furthermore, considering that people have adopted a pattern of predominantly semisolid diet consistency since the 20 th century, significant loss of proximal enamel due to masticatory forces is seen more frequently in elderly patients. [18][19][20] Concerning sexual dimorphism, a study reported that mesiodistal crown measurements were larger for men, compared with the dimensions obtained for women. 21 Some authors assessed the mesiodistal and buccolingual crown dimensions in North Americans, Egyptians and Mexicans.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, considering that people have adopted a pattern of predominantly semisolid diet consistency since the 20 th century, significant loss of proximal enamel due to masticatory forces is seen more frequently in elderly patients. [18][19][20] Concerning sexual dimorphism, a study reported that mesiodistal crown measurements were larger for men, compared with the dimensions obtained for women. 21 Some authors assessed the mesiodistal and buccolingual crown dimensions in North Americans, Egyptians and Mexicans.…”
Section: Discussionmentioning
confidence: 99%
“…That this is indeed the case for primate molars is seen, for example, in the crown structure of species with comparatively enhanced molar wear, wherein the 'functional' side of the tooth exhibits not only thicker enamel but also a lower cervical position (or higher crown) (e.g. Molnar and Gantt, 1977;Shimizu, 2002), thereby providing relatively more tooth material available for wear in the 'functional' side of the molar. However, an additional interest of ours is to evaluate fossil specimens and species, with which, more often than not, neither whole crown distributions of enamel nor extensive series of measurements at precisely defined locations of the tooth are possible.…”
Section: Utility Of Linear Measures Of Enamel Thickness In Interspecimentioning
confidence: 94%
“…Physical cross-sections of molar teeth have been used to measure enamel thickness by a number of workers (e.g., Molnar and Gantt, 1977;Martin, 1985;Beynon and Wood, 1986;Grine and Martin, 1988;Macho and Berner, 1993;Dumont, 1995;Schwartz, 2000b;Grine, 2002Grine, , 2004Grine, , 2005Grine et al, 2005). Physical sections provide an accurate portrayal of enamel thickness in a particular plane of section, but problems with specimen orientation (i.e., section obliquity) may render some of these data less than ideal.…”
mentioning
confidence: 99%